Extracting and analysising anthocyanin content from different plants - Thanh Nhan, Pham Thi; Cuong, Nguyen Huy; Binh, Le Tran (Academia Journal of Biology, 2012)
Anthocyanins are natural pigments used safely in foods and functional food. They play the important role in photoprotection, antioxidant activity, biological defense and also in symbiotic functions between microbes and plant cells. In addition, they are attractants for pollinating via flower color and dispersing seeds via brightly colored fruit. This article presents some anthocyanin extraction buffers and the result of determination of anthocyanin content in different plants by pH-differential method. Using the buffer containing acetone and 0.01% HCl to extract anthocyanin from different materials was more effective than three other types of buffers (ethanol: distilled water with HCl 1% (1v: 1v), methanol with 0.1% HCl (v/v), methanol with 0.01% HCl (v/v)) and the absorption spectrum of anthocyanin diluted extract was similar to that of standard anthocyanin. Maximum absorption spectrum of the different diluted extracts was ranged from 511nm to 540nm. In addition, the nonomeric anthocyanin pigment is in inverse proportion to the percent of polymeric color. The content of anthocyanin was 0.59% in young stem of Zea mays L., 1.49% in leaf of Hibiscus sabdariffa L., 0.34% in flower of Musa paradisiaca L., 0.56% in leaf of Chloranthus spicatus (Thunb.) Makin, 1.28% in leaf of Cordyline fruticosa (L.) Goepp., 1.75% in fruits of Morus alba L., 1.72% in leaf of Perilla frutescens (L.) Britt., 0.46% in tuber of Ipomoea batatas (L.) Poir., 1.27% in fruit skin of Vitis vinifera L., 1.05% in leaf of Paederia scandens (Lour.) Merr., 2.04% in bulbus of Eleutherine bulbosa (Mill.) Urban and 1.74% in leaf of Amaranthus tricolor L..